2004
DOI: 10.1038/sj.bjc.6601970
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cerebral metastases in patients treated with trastuzumab for metastatic breast cancer

Abstract: Trastuzumab is an effective treatment for patients with metastatic breast cancer (MBC) that overexpresses HER-2. A high incidence of brain metastases (BM) has been noted in patients receiving trastuzumab. A retrospective chart review was conducted of 100 patients commencing trastuzumab for metastatic breast cancer from July 1999 to December 2002, at the Christie Hospital. Seven patients were excluded; five patients developed central nervous system metastases prior to starting trastuzumab, and inadequate data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
194
3
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(220 citation statements)
references
References 23 publications
17
194
3
4
Order By: Relevance
“…Cumulative 3-year risk of brain relapse of 42% is in the range found in other series of HER2-positive advanced breast cancer patients [11][12][13][14][15][16][17]23]. In this cohort the average annual risk of symptomatic brain relapse for surviving patients during consecutive 7 years of follow-up was 10%, with no apparent plateau.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Cumulative 3-year risk of brain relapse of 42% is in the range found in other series of HER2-positive advanced breast cancer patients [11][12][13][14][15][16][17]23]. In this cohort the average annual risk of symptomatic brain relapse for surviving patients during consecutive 7 years of follow-up was 10%, with no apparent plateau.…”
Section: Discussionsupporting
confidence: 68%
“…The small number of patients not administered trastuzumab calls for cautious interpretation of this result, nevertheless resistance of brain lesions to trastuzumab therapy was consistently reported by others. Notably, several studies demonstrated the development of brain metastases despite the response to trastuzumab in extracranial sites, and no prophylactic effect of trastuzumab on brain relapse both in advanced disease and in the adjuvant setting [11][12][13][14][15][16][17]. Brain is the sole site of progression in about 10% of advanced breast cancer patients administered trastuzumab [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,5,6 In addition, the higher incidence may be caused by clonal selection induced by novel therapeutic agents like Herceptin. [7][8][9][10] Because diagnostic imaging procedures will usually only be performed after clinical symptoms have become manifest, identification of risk factors for CNS involvement could enable specific surveillance and management of patients at risk. Indicators of an increased risk for CNS metastases have been described such as young age at diagnosis, diseasefree interval less than 1 year, oestrogen receptor (ER) or progesterone receptor (PR) negativity, 11 and Her-2/neu amplification.…”
Section: Introductionmentioning
confidence: 99%
“…Z drugiej strony w rejestrze prowincji Parma czas do pojawienia się przerzutów do mózgu u chorych na HER2--dodatniego raka leczonych i nieleczonych trastuzumabem wynosił odpowiednio 20,3 i 10,3 miesiąca (p = 0,018), co wynika jednak z aktywności tego leku poza ośrodkowym układem nerwowym [3]. Z kolei u chorych na HER2-dodatniego, zaawansowanego raka piersi skumulowane ryzyko wystąpienia objawowych przerzutów do mózgu szacuje się na 10-40% [3,[5][6][7][8][9][10][11][12][13][14], a średnie roczne ryzyko na około 10% [14]. Podobnie jak w leczeniu uzupełniającym, leczenie trastuzumabem w rozsianym raku piersi znacząco opóźnia ujawnienie się objawowych przerzutów do mózgu (w badaniu Dawood i wsp.…”
unclassified